(untitled) (Swiss Medical Weekly, 2013)
PRINCIPLES: Unnecessary treatment of asymptomatic bacteriuria and overuse of urinary catheters in hospitals are of concern regarding antimicrobial resistance and patient safety, respectively. We investigated the effectiveness of a multifaceted intervention in reducing urinary catheter use and unnecessary prescription of antibiotics for asymptomatic bacteriuria in hospitalised patients in a clinic for internal medicine. METHODS: Data were collected retrospectively from all inpatients during a 3-month period both before and after a multifaceted intervention from the Clinic for Internal Medicine of our secondary care hospital. The intervention consisted of implementation of guidelines, establishment of a standard for urinary catheter management, introduction of restricted orders and a reminder of indwelling catheters, as well as lectures and internet-based learning focusing on asymptomatic bacteriuria. RESULTS: The incidence rate of urinary catheter days decreased significantly from 27 to 17 catheter days per 100 patient days (incidence rate ratio 0.61, 95% confidence interval 0.57–0.67). The incidence rate of unnecessary antibiotic treatment days for asymptomatic bacteriuria dropped significantly from 22 to 10 treatment days per 1,000 patient days (incidence rate ratio 0.46, 95% confidence interval 0.33–0.63). CONCLUSIONS: A multifaceted intervention was effective in reducing both urinary catheter days and inappropriate antibiotic use for asymptomatic bacteriuria.